2014
DOI: 10.1007/978-3-319-09147-1_23
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Land Cover Change in a Mediterranean Catchment at Different Time Scales

Abstract: Land cover has been changing rapidly throughout the world, and this issue is important to researchers, urban planners, and ecologists for sustainable land cover planning for the future. Many modeling tools have been developed to explore and evaluate possible land cover scenarios in future and time scales vary greatly from one study to another. The main objective of this study is to test land cover change prediction at different time scales in a Mediterranean catchment in SE France. Land cover maps were created… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…The transition potential map for each transition was produced and the LULCs for 2014 were modeled. Previous studies have found MLPM to produce better prediction accuracies in areas featuring stable and slow LULC changes [48]. Finally, in the SM model, Markovian conditional probability images from the years 1990 to 2002 were produced using the Markov module of IDRISI.…”
Section: Modeling the Land Cover For 2026mentioning
confidence: 99%
“…The transition potential map for each transition was produced and the LULCs for 2014 were modeled. Previous studies have found MLPM to produce better prediction accuracies in areas featuring stable and slow LULC changes [48]. Finally, in the SM model, Markovian conditional probability images from the years 1990 to 2002 were produced using the Markov module of IDRISI.…”
Section: Modeling the Land Cover For 2026mentioning
confidence: 99%
“…It is embedded in the IDRISI software [7], where only thematic raster images with the same land cover categories listed in the same sequential order can be input for LULCC analysis [15]. LCM evaluates land cover changes between two different times, calculates the changes, and displays the results with various graphs and maps.…”
Section: Introductionmentioning
confidence: 99%
“…LCM evaluates land cover changes between two different times, calculates the changes, and displays the results with various graphs and maps. Then, it predicts future LULC maps on the basis of relative transition potential maps [15] relying upon Multi-Layer Perceptron (MLP) neural networks [16]. LCM was found to produce better prediction accuracy in short time scales, especially in the case of stable land covers rather than cases of rapid change [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Change detection is the concept of identifying contrasts or discrepancies in the state of an object or phenomenon by observing it at different times [32]. Change detection studies are centred on identifying the biotic and abiotic components of the spectral and temporal changes that are occurring within ecosystems [33]. It involves the ability to quantify temporal alteration and transformation using multi-temporal data sets.…”
Section: Introductionmentioning
confidence: 99%